2010
DOI: 10.1159/000312718
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Continuing Education Program on Pharmacists’ Knowledge and Attitudes toward Asthma Patient Care

Abstract: Objective: The objective of this study was to evaluate the impact of an asthma continuing education program on pharmacists’ knowledge and attitudes related to asthma pharmaceutical care. Subjects and Methods: A 20-hour continuing education program was conducted by the joint efforts of the Taipei City Government, Taiwan Association of Asthma Education and Taipei Medical University Wan Fang Hospital, in a series of 4 days afternoon sessions from June 26 to July 4, 2004. One hundred and twenty-five pharmacists pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
(26 reference statements)
0
23
0
Order By: Relevance
“…Finally, full-text articles were retrieved for review, and 19 articles met the eligibility criteria and were included in this systematic review (Figure 1). [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Most the articles were published from 2000 to 2013 (n518). One study was published in 1997.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, full-text articles were retrieved for review, and 19 articles met the eligibility criteria and were included in this systematic review (Figure 1). [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Most the articles were published from 2000 to 2013 (n518). One study was published in 1997.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the CE programs (n513) had their content areas chosen by the researchers who conducted the studies without assessing gaps in knowledge or the self-reported educational needs of the community pharmacists. 22,23,25,26,[28][29][30][32][33][34][35][36][37] Most of the studies (n514) [21][22][23][24][25][26][27][28][29][30][31][32][33][34] used just one media method in the CE program. The live method was the most frequent (n511), [21][22][23][24][25][26][27][28][29][30][31] followed by the Internet (nonreal time; n52), 32,33 and print (n51) 34 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations